If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 42 = 10x + 50 Reorder the terms: 42 + 12x = 10x + 50 Reorder the terms: 42 + 12x = 50 + 10x Solving 42 + 12x = 50 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 42 + 12x + -10x = 50 + 10x + -10x Combine like terms: 12x + -10x = 2x 42 + 2x = 50 + 10x + -10x Combine like terms: 10x + -10x = 0 42 + 2x = 50 + 0 42 + 2x = 50 Add '-42' to each side of the equation. 42 + -42 + 2x = 50 + -42 Combine like terms: 42 + -42 = 0 0 + 2x = 50 + -42 2x = 50 + -42 Combine like terms: 50 + -42 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 17x-1=135 | | X^2-20-3x-20=0 | | 12x-6+6=36 | | 1/-76=1/x | | -2x+8=4(x+8) | | 7=(-3)+x | | 12x+42=10x+56 | | 0.4+8=12 | | -9=2(w+3)-5w | | 3-(2x+2)=x-(3x-5) | | 4+7(x-8)=9-3(x-4) | | 1-4y=1 | | -14=-4+5x+3x | | 33m-14+14=33 | | x-7=34-7(x+7) | | 4x-1=113 | | 124-v=185 | | -7+3y=-16 | | 16+8y=80 | | 4v-4=-24 | | 2(x-4)-3=7-4x | | 3=(-6)+x | | -5p=0 | | -x-10y=-24 | | 56=2(15)+2w | | -2y+30=5y-5 | | 3x+5x+-4=-14 | | 5+2*[3(x+5)-(3x+11)]=11-4x | | 3x+3x+4x+2x= | | 2-4d=0 | | 3y-5t+10=36 | | -5/9y25 |